Family structure and child cognitive outcomes: Evidence from Canadian longitudinal data - Ana M. Ferrer; Yazhuo Pan (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2018)
This study investigates the role of family structure on cognitive outcomes of children. Using the rich panel data information from the National Longitudinal Survey of Children and Youth (NLSCY), collected on children and their families biennially since 1994, we investigate the association between a child's math & reading performance and family structure and changes in family structure. We find that children who stay-in or move-to non-intact families have lower reading scores than those who stay in intact families. Although initial findings indicate that family structure appears to have overall little effect on children's math performance, analysis by gender reveals that girls' performance appears to be more affected than boys' by their parents' divorce/remarriage or the presence of step-family members. Moreover, analysis by heritage reveals that family structure affects the math performance of children of French heritage differently from those of other Canadian heritage, while the impact on reading scores is similar between these two groups. A similar result follows our analysis of religious groups. The impact of family structure differs between children in Catholic families and those in Non-Catholic families for math performance, but is similar for reading performance.
Keywords: J12; J13; J16; I20; Z12; 330; Family structure; transition in family structure; family instability; academic performance of children